Application of two problem solving cycles to students' higher-order thinking skills on reproductive system material - Sekar Wiji Utami; Ari Sunandar; Arif Didik Kurniawan (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Two problem solving cycles are problem-based learning with two learning cycles that can improve students' higher order thinking skills. The knowledge of reproductive health is needed by the student, due to the student as future generation must be ready to facing the reproductive health problem in the future. This study aimed to determine the differences in learning two problem solving cycles on students' higher-order thinking skills. The population of this study were students of SMA Negeri 02 Sekayam-West Kalimantan with a sample of class XI IPA 1 and XI IPA 2. Students were given 12 questions as essay test in the beginning and end of the cycles. Data were analyzed using the Mann Whitney U test. Research shows that there are significant differences in learning towards higher-order thinking skills with learning two problem solving cycles (sig. 0.015 < 0.05). Hence, it could be concluded that two problem solving cycles could be applied in learning material on the reproductive system.